A Rare Case of 7 Simultaneous Arterial Dissections and Review of The Literature. (October 2019) - Amitai Komem, Daphna; Sukenik Halevy, Rivka; Griton, Yigal; Shnaker, Ali; Levy, Yair; Weissmann, Jonathan; Fajer, Simone
Objective: Spontaneous multiple artery dissection is a relatively rare phenomenon. Early clinical signs are often nonspecific, making it difficult to diagnose. Case Report: This is a case of a 51-year-old female who presented with spontaneous dissection of 4 visceral arteries, both iliac arteries, and of the right internal carotid artery. The patient underwent urgent successful endovascular repair. Later complications included acute respiratory distress syndrome and pneumonia after massive blood transfusion. She recovered gradually and was discharged after 21 days. Due to this rare presentation, genetic investigation was performed in search of a connective tissue disorder. Results revealed a new COL3A1 subtype mutation. The pathogenicity of this variant remains unclear. Conclusion: We recommend a high index of suspicion for visceral artery dissection in the differential diagnosis for abdominal pain with concurrent uncontrolled hypertension. Early diagnosis and intervention are crucial to reducing the mortality rate.